2016
DOI: 10.1007/s00403-016-1635-x
|View full text |Cite
|
Sign up to set email alerts
|

Does hypoxia play a role in infantile hemangioma?

Abstract: Infantile hemangioma (IH), the most common tumor of infancy, is characterized by rapid growth during infancy, followed by spontaneous involution over 5-10 years. Certain clinical observations have led to the suggestion that IH is triggered and maintained by hypoxia. We review the literature on the possible role of hypoxia in the etiology of IH, in particular, (1) the role of hypoxia inducible factor-1α (HIF-1α) and its downstream targets including GLUT-1 and VEGF; (2) the pathophysiological link between IH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 70 publications
1
71
0
1
Order By: Relevance
“…If this was the case, the 5‐year delay for these lesions to become symptomatic could be consistent with the age of first occurrence of DLs reported in the literature . Another potential explanation is the development of DLs in the context of localized hypoxia secondary to regional anomalous vascular development . And finally, the use of rapamycin and/or prolonged (3 years) antiangiogenic, multimodality treatment potentially altered the natural involution process of IHs with “rebound” angiogenesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…If this was the case, the 5‐year delay for these lesions to become symptomatic could be consistent with the age of first occurrence of DLs reported in the literature . Another potential explanation is the development of DLs in the context of localized hypoxia secondary to regional anomalous vascular development . And finally, the use of rapamycin and/or prolonged (3 years) antiangiogenic, multimodality treatment potentially altered the natural involution process of IHs with “rebound” angiogenesis.…”
Section: Discussionsupporting
confidence: 77%
“…3 Another potential explanation is the development of DLs in the context of localized hypoxia secondary to regional anomalous vascular development. 15,16 And finally, the use of rapamycin and/or prolonged (3 years) antiangiogenic, multimodality…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of segmental IH of the extremities seems to follow patterns related to arterial supply. It is hypothesized that IH develops in response to local tissue or systemic hypoxia in an attempt at revascularization . Reimer et al hypothesized that variant arterial anatomy during embryo‐fetal development might contribute to temporary regional hypoxia, thus stimulating angiogenesis resulting in IH.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that IH develops in response to local tissue or systemic hypoxia in an attempt at revascularization. 11,13 Reimer et al 12 hypothesized that variant arterial anatomy during embryo-fetal development might contribute to temporary regional hypoxia, thus stimulating angiogenesis resulting in IH. Moreover, the embryologic delay regarding the formation of leg buds compared to arm buds might explain the higher prevalence of IH-MAG on the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…7 Both previous studies and physical manifestations have indicated the presence of hypoxic condition and its promotive role in IH. 8,9 However, the precise mechanism accounting for hypoxia-mediated IH progression has not been fully clarified. Therefore, it is essential to discover novel molecular events underlying this process, which may provide better insights into the biological course of IH.…”
Section: Research-article2017mentioning
confidence: 99%